2012
DOI: 10.1007/s00391-011-0279-x
|View full text |Cite
|
Sign up to set email alerts
|

RAGE influences obesity in mice

Abstract: These data suggest that RAGE is involved in the development of obesity and insulin resistance.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
12
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 38 publications
(13 citation statements)
references
References 28 publications
0
12
0
Order By: Relevance
“…The findings are consistent with those of Monden et al (28) where RAGE null mice fed HFD (20% of total calories from cocoa butter and 0.15% from cholesterol) were protected from diet-induced obesity and insulin resistance and confirm the finding that RAGE contributes to regulation of adipocyte hypertrophy. In contrast, Leuner et al (29) reported that RAGE null mice fed an HFD (60% of calories from fat) displayed greater obesity versus the WT cohort. However, Leuner et al did not test the specific effects of RAGE expression in hematopoietic cells or the effects of RAGE antagonism.…”
Section: Discussionmentioning
confidence: 92%
“…The findings are consistent with those of Monden et al (28) where RAGE null mice fed HFD (20% of total calories from cocoa butter and 0.15% from cholesterol) were protected from diet-induced obesity and insulin resistance and confirm the finding that RAGE contributes to regulation of adipocyte hypertrophy. In contrast, Leuner et al (29) reported that RAGE null mice fed an HFD (60% of calories from fat) displayed greater obesity versus the WT cohort. However, Leuner et al did not test the specific effects of RAGE expression in hematopoietic cells or the effects of RAGE antagonism.…”
Section: Discussionmentioning
confidence: 92%
“…This implication is mostly related to its capacity to interact with advanced glycation end products (AGE) [51]. AGE can signal through RAGE to activate oxidative stress and inflammation and finally interfere with insulin-signaling pathways in adipocytes to decrease insulin sensitivity [52], [53].…”
Section: Discussionmentioning
confidence: 99%
“…( 51 , 72 , 79 ) Glyoxal, MDA and hydroxynonenal (HNE) are products of peroxidation lipids. ( 72 , 80 , 81 ) Table 1 outlines the various classes of AGEs. ( 73 , 82 , 83 ) It is now known that endogenous AGEs contribute to aging, CVD, kidney disease, diabetes, Alzheimer’s disease (AD), cataracts, autoimmune diseases, allergies, endocrine disorders and gastrointestinal disturbances.…”
Section: Advanced Glycation End-productsmentioning
confidence: 99%